Histopathological Characterization and Whole Exome Sequencing of Ectopic Thyroid: Fetal Architecture in a Functional Ectopic Gland from Adult Patient - Rosalinda Yasato Camargo; Cristina Takami Kanamura; Celso Ubirajara Friguglietti; Célia Regina Nogueira; Sonia Iorcansky; Alfio José Tincani; Ana Karina Bezerra; Ester Brust; Fernanda Christtanini Koyama; Anamaria Aranha Camargo; Fernanda Orpinelli R. Rego; Pedro Alexandre Favoretto Galante; et al. (International Journal of Endocrinology)
Ectopic thyroid results from a migration defect of the developing gland during embryogenesis causing congenital hypothyroidism. But it has also been detected in asymptomatic individuals. This study aimed to investigate the histopathological, functional, and genetic features of human ectopic thyroids. Six samples were histologically examined, and the expression of the specific thyroid proteins was assessed by immunohistochemistry. Two samples were submitted to whole exome sequencing. An oropharynx sample showed immature fetal architecture tissue with clusters or cords of oval thyrocytes and small follicles; one sample exhibited a normal thyroid pattern while four showed colloid goiter. All ectopic thyroids expressed the specific thyroid genes and T4 at similar locations to those observed in normal thyroid. No somatic mutations associated with ectopic thyroid were found. This is the first immature thyroid fetal tissue observed in an ectopic thyroid due to the arrest of structural differentiation early in the colloid stage of development that proved able to synthesize thyroid hormone but not to respond to TSH. Despite the ability of all ectopic thyroids to synthetize specific thyroid proteins and T4, at some point in life, it may be insufficient to support body growth leading to hypothyroidism, as observed in some of the patients.